PEMANFAATAN ASAP CAIR KAYU SENGON UNTUK PENGAWETAN KAYU PADA KELOMPOK PENGRAJIN KAYU DI MRANGGEN, KABUPATEN DEMAK - Niken Subekti; Sonika Maulana; Nina Oktarina; Aprilia Findayani; Saniaturrohmah Saniaturrohmah; Shinta Hedy Cahyanningrum (Dinamika Journal : Pengabdian Masyarakat, 2020)
The development of public awareness on the dangers of pesticides as preservatives demands environmentally friendly preservatives production. It is a great opportunity to develop and produce natural wood preservatives from Sengon wood waste (Paraserianthes falcataria). This community service program aims to improve the production of natural wood preservatives made from good quality Sengon wood waste which is safe for the environment. The method used is the application of prototype manufacturing of pilot plan scale wood vinegar to increase the production of ready commercial use natural preservatives. This community service activity will produce wood preservatives based on consistent quality Sengon wood waste, increased production capacity and increase the efficiency of timbers.